La literatura en la perspectiva de la ecocrítica - Camasca, Edwin (2020)
The paper addresses the fundamentals of ecocriticism and its link to the study of literature. The purpose of the text is to explain the principles, porposals and objectives of ecocriticism,as well as its contribution to the formation of a critical awareness about environmental issues. From the perspective of ecocriticism, literary Works illustrate the existence of serious environmental problems, demonstrate the action of man in the process of the destruction of nature, reveal the utilitarian attitude that characterizes the exploitation of natural resources and highlights the lack of a true commitment of the human being with his hábitat. Through a review of Spanish and Latin Americcan literature, the paper analyzes the characteristics of the man-nature relationship within the framework of ecocriticism. In that perspective, this relationship is fundamental in the poetry of the native peoples, as expressed in the voice of the Mapuche poets.